SOX, corporate transparency, and the cost of debt - Andrade, Sandro (Institutional Knowledge at Singapore Management University, 2014)
We investigate the impact of the Sarbanes–Oxley (SOX) Act on the cost of debt through its effect on the reliability of financial reporting. Using Credit Default Swap (CDS) spreads and a structural CDS pricing model, we calibrate a firm-level corporate opacity parameter in the pre- and post-SOX periods. Our analysis shows that corporate opacity and the cost of debt decrease significantly after SOX. The median firm in our sample experiences an 18 bp reduction on its five-year CDS spread as a result of lower opacity following SOX, amounting to total annual savings of $ 844 million for the 252 firms in our sample. Furthermore, the reduction in opacity tends to be larger for firms that in the pre-SOX period have lower accrual quality, less conservative earnings, lower number of independent directors, lower S& P Transparency and Disclosure ratings, and are more likely to benefit from SOX-compliance according to Chhaochharia and Grinstein’s (2007) criteria.